2022
DOI: 10.9734/ajaar/2022/v19i4383
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Correlation and Path Coefficient Analysis in Hybrid Maize (Zea mays L.)

Abstract: The goal of the current investigation was to determine correlation coefficient, path analysis and genetic variability among twenty four maize hybrids for ten characters in a Randomized Block Design (RBD) with three replications at the research field of Plant Breeding Division, Regional Agricultural Research Station, Barisal, Bangladesh Agricultural Research Institute (BARI), Bangladesh during rabi season of 2014-15. The measured traits were Days to 50% tasseling (DT), days to 50% silking (DS), anthesis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The traits in this study showed a highly significant positive relationship with each other in terms of genotypic and phenotypic correlations, and the genotypic correlation coefficients were greater than the phenotypic correlation coefficients. These findings indicate that the association was due to genetic factors [ [71] , [72] , [73] ] and that these are important characteristics that could be utilized as criteria for selecting for wheat plants under saline conditions. Among these relationships, TDW, SDW, TFW, and SFW demonstrated stronger relationships with each other in terms of both genotypic and phenotypic relationships ( Table 6 ), confirming that shoot biomass contributes more to total biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The traits in this study showed a highly significant positive relationship with each other in terms of genotypic and phenotypic correlations, and the genotypic correlation coefficients were greater than the phenotypic correlation coefficients. These findings indicate that the association was due to genetic factors [ [71] , [72] , [73] ] and that these are important characteristics that could be utilized as criteria for selecting for wheat plants under saline conditions. Among these relationships, TDW, SDW, TFW, and SFW demonstrated stronger relationships with each other in terms of both genotypic and phenotypic relationships ( Table 6 ), confirming that shoot biomass contributes more to total biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The high yield is attributed to the high dry matter accumulation and mobilization attributed to the high number of leaves per plant. Also, traits including plant stand, leaf area index, ear aspect, number of ears per plant, ear length, the number of kernel rows per ear, above‐ground biomass, shelling percentage and 1000‐kernel weight are positively correlated and confer a high positive direct effect on grain yield (Adu et al, 2016; Rafiq et al, 2010). The above selection procedure saves breeding costs and allows a simultaneous selection of economic traits to enhance grain yield rather than aiming for genomic selection for each trait.…”
Section: Enablers Of Genomic Selectionmentioning
confidence: 99%